The (un)demand for money in Canada - Geoffrey Dunbar; Casey Jones (Bank of Canada, 2018)
A novel dataset from the Bank of Canada is used to estimate the deposit functions for banknotes in Canada for three denominations: 1,000, 100 and 50. The broad flavour of the empirical findings is that denominations are different monies, and the structural estimates identify the underlying sources of the non-neutrality. There is evidence of large and significant deposit costs for the highest-value denomination, the 1,000 banknote, but insignificant costs for the 100 and 50 denominations. The results imply that the interest rate elasticity of deposit is positive for the 1,000 but negative for the 100 and the 50. Third, 5 percent of the 1,000, 30 percent of the 100 and 22 percent of the 50 banknotes ever issued by the Bank of Canada do not circulate through financial institutions (in Canada). Finally, we find evidence that the Lehman Brothers crisis increased the deposit probability by a factor of 2-3 for the 1,000 banknote for a majority of the population in Canada.
Keywords: E41; C31; C36; 330; Bank notes; Econometric and statistical methods